A New Definition for Intracranial Compliance to Evaluate Adult Hydrocephalus After Shunting - Gholampour, Seifollah; Yamini, Bakhtiar; Droessler, Julie; Frim, David (Frontiers in Bioengineering and Biotechnology, 2022)
The clinical application of intracranial compliance (ICC), ∆V/∆P, as one of the most critical indexes for hydrocephalus evaluation was demonstrated previously. We suggest a new definition for the concept of ICC (long-term ICC) where there is a longer amount of elapsed time (up to 18 months after shunting) between the measurement of two values (V1 and V2 or P1 and P2). The head images of 15 adult patients with communicating hydrocephalus were provided with 9 sets of imaging in 9 stages: prior to shunting, and 1, 2, 3, 6, 9, 12, 15, and 18 months after shunting. In addition to measuring CSF volume (CSFV) in each stage, intracranial pressure (ICP) was also calculated using fluid-structure interaction simulation for the non-invasive calculation of ICC. Despite small increases in the brain volume (16.9%), there were considerable decreases in the ICP (70.4%) and CSFV (80.0%) of hydrocephalus patients after 18 months of shunting. The changes in CSFV, brain volume, and ICP values reached a stable condition 12, 15, and 6 months after shunting, respectively. The results showed that the brain tissue needs approximately two months to adapt itself to the fast and significant ICP reduction due to shunting. This may be related to the effect of the “viscous” component of brain tissue. The ICC trend between pre-shunting and the first month of shunting was descending for all patients with a “mean value” of 14.75±0.6 ml/cm H2O. ICC changes in the other stages were oscillatory (non-uniform). Our non-invasive long-term ICC calculations showed a non-monotonic trend in the CSFV-ICP graph, the lack of a linear relationship between ICC with ICP, and an oscillatory increase in ICC values during shunt treatment. The oscillatory changes of long-term ICC may reflect the clinical variations in hydrocephalus patients after shunting.